2001
DOI: 10.1046/j.1444-2906.2001.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinomotor responses of juvenile bluefin tuna Thunnus thynnus

Abstract: SUMMARY: In bluefin tuna culture, a high mortality of juveniles is caused by bumping into the tank and net‐pen walls at dawn. This bumping can possibly be attributed to visually disoriented behavior of the fish. To examine this possibility, the authors carried out retinomotor response experiments with juvenile bluefin tuna (50.7–96.8 mm total length, at which they were transferred from a indoor tank to a sea net‐pen) and measured ambient light intensity at the culture site at dawn. The light intensity at which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 12 publications
1
33
1
3
Order By: Relevance
“…Such conditions can result in aggregations of fish that are sufficiently high to cause collisions and seriously deplete oxygen concentrations (Johansson et al 2006;Chapter 4). In other cases, problems arise because natural stimuli that are important in guiding fish behaviour are absent in culture systems, as when juvenile bluefin tuna (Thunnus thynnus), which do not see well in dim light, collide with tank or cage walls and injure themselves at the low light intensities that occur around dawn (Ishibashi et al 2009;Masuma et al 2001;Chapter 4). An additional example is seen in young guppies (Poecilia reticulata), which fail to forage efficiently on zooplankton when the light to which they are exposed lacks long wavelengths (White et al 2005;Chapter 5).…”
Section: Effects Of the External Stimuli That Control Behaviourmentioning
confidence: 99%
“…Such conditions can result in aggregations of fish that are sufficiently high to cause collisions and seriously deplete oxygen concentrations (Johansson et al 2006;Chapter 4). In other cases, problems arise because natural stimuli that are important in guiding fish behaviour are absent in culture systems, as when juvenile bluefin tuna (Thunnus thynnus), which do not see well in dim light, collide with tank or cage walls and injure themselves at the low light intensities that occur around dawn (Ishibashi et al 2009;Masuma et al 2001;Chapter 4). An additional example is seen in young guppies (Poecilia reticulata), which fail to forage efficiently on zooplankton when the light to which they are exposed lacks long wavelengths (White et al 2005;Chapter 5).…”
Section: Effects Of the External Stimuli That Control Behaviourmentioning
confidence: 99%
“…Masuma et al (2001) suggested that one of the causes for the bumping is visual disorientation due to the incompatibility of the retinal adaptation with the change in the ambient light intensity at dawn. PBT in captivity have less diseases, with the exception of an iridovirus disease which breaks out in yearling tuna kept at temperatures over 21 ºC (Sawada, 2005).…”
Section: Management Of Broodstockmentioning
confidence: 99%
“…Miyashita [3] investigated the development of external morphology concerning swimming performance and found that BFT attain remarkable propulsion power from the juvenile period to the young stage, but their control system for swimming develops later, resulting in an inability to avoid tank walls. Masuma [4] carried out retinomotor response experiments using cultured BFT juveniles and concluded that visual disorientation due to incompatibility of retinal adaptation with the change in ambient light intensity at dawn is one of the causes of net-pen wall collisions. Torisawa [5] also examined the effect of light intensity on schooling behavior and retinal light adaptation of juvenile Pacific BFT in a water tank.…”
Section: Introductionmentioning
confidence: 99%